An Integrated Approach to Counseling Children Diagnosed With ADHD, ODD, and Chronic Stressors. (January 2018) - Wofford, Joseph Rufus; Ohrt, Jonathan H.
Families in rural, low socioeconomic status areas are often underserved related to mental health services. Additionally, attention deficit hyperactive disorder (ADHD) and oppositional defiant disorder (ODD) are common comorbid concerns for children in these areas. Further, chronic stressors are typically present in the lives of children in such a setting when a parent loses custody of the child, and another family member takes on the parenting role. In this article, we (a) review information on the confluence of ADHD, ODD, and chronic stressors; (b) present an assimilative integrated approach using behavioral therapy as the foundational theory, supplemented by techniques from play therapy and structural family therapy; and (c) present a case example in which the approach was utilized.